Investigation of Hazard Potential of Oil Industry Wastes and Products for Better Management Practices - Bolat, Dilek; Can-Guven, Emine; Gedik, Kadir; Kurt Karakuş, Perihan Binnur (Asce-Amer Soc Civil Engineers, 2018)
Polychlorinated biphenyl (PCB), metal, and chlorine contents of samplesincluding waste mineral oil, engine oil, edible oil, oily waste (industrial/domestic), and number 10 lube (NTL)were investigated to evaluate possible hazards to the environment. Analyses were conducted using Turkish and United States Environmental Protection Agency standards. The results showed an uneven distribution of pollutants among all type of samples or samples that were collected from the same area at different time intervals. Although PCB usage was banned in Turkey many years ago, indicator PCB congeners were observed in NTL samples that were predominantly used as alternative fuel in heavy duty diesel engines. Waste oil and oily waste samples should be recycled as raw materials and/or recovered as an energy source, but the findings of this study yields disposal as a hazardous material due to high metal (Cr) content. The overall results of the study show that uncontrolled combustion of waste oil and oily wastes may cause environmental problems, and use of these wastes and products should be controlled and managed by strict precautions.
Keywords: Alternative fuel; Combustion; Diesel engine; Emission; Air pollution; Number 10 lube